2016
DOI: 10.1016/j.celrep.2016.04.031
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Cellular Disease Models Reveal Synergistic Interaction of Trisomy 21 and GATA1 Mutations in Hematopoietic Abnormalities

Abstract: Chromosomal aneuploidy and specific gene mutations are recognized early hallmarks of many oncogenic processes. However, the net effect of these abnormalities has generally not been explored. We focused on transient myeloproliferative disorder (TMD) in Down syndrome, which is characteristically associated with somatic mutations in GATA1. To better understand functional interplay between trisomy 21 and GATA1 mutations in hematopoiesis, we constructed cellular disease models using human induced pluripotent stem c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
124
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 85 publications
(136 citation statements)
references
References 37 publications
12
124
0
Order By: Relevance
“…We previously generated a patient-derived trisomy 21 iPSC (‘Tri21-GATA1wt’ iPSC) line that contains one paternal and two maternal copies of chromosome 21 (Supplementary Fig. S1), and a partial trisomy 21 iPSC (‘Partial-Tri21-GATA1wt’ iPSCs) line (hereafter referred to as ‘Tri21’ iPSCs and ‘Partial-Tri21’ iPSCs, respectively) 17 . In this Partial-Tri21 iPSC line, a 4-Mb region on HSA21 was selectively deleted only from the paternal chromosome 21 in Tri21 iPSCs, so these genetically modified cells can be used to clarify the parental origin of chromosome 21.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We previously generated a patient-derived trisomy 21 iPSC (‘Tri21-GATA1wt’ iPSC) line that contains one paternal and two maternal copies of chromosome 21 (Supplementary Fig. S1), and a partial trisomy 21 iPSC (‘Partial-Tri21-GATA1wt’ iPSCs) line (hereafter referred to as ‘Tri21’ iPSCs and ‘Partial-Tri21’ iPSCs, respectively) 17 . In this Partial-Tri21 iPSC line, a 4-Mb region on HSA21 was selectively deleted only from the paternal chromosome 21 in Tri21 iPSCs, so these genetically modified cells can be used to clarify the parental origin of chromosome 21.…”
Section: Resultsmentioning
confidence: 99%
“…Next, we differentiated the healthy control disomy 21 (Di21), trisomy 21 (Tri21) and corrected disomy 21 iPSC lines into haematopoietic lineages to evaluate their haematopoietic differentiation potential. Recently, we have reported that trisomy 21 augments foetal haematopoiesis through the acceleration of early haematopoietic commitment 17 . The proportion of CD43 + cells in the CD34 + CD38 − Lin − fraction, which represents committed haematopoietic progenitors, was significantly increased in the Tri21 iPSC line compared with that in the Di21 iPSC lines, as reported previously (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…ES-sac-mediated in vitro hematopoietic differentiation analyses using the DS models revealed that Ts21 and the GATA1 mutations synergistically contributed to hematopoietic abnormalities. Although another group established isogenic cell lines via the spontaneous loss of chromosome 21 from induced pluripotent stem (iPS) cells derived from a DS patient, they reported the synergistic interaction of Ts21 and GATA1 mutations mainly from an assessment of nonisogenic cell lines with a different genotype [96]. It is crucial to establish isogenic cell lines for disease models harboring chromosome abnormalities.…”
Section: In Vitro Models For Aneuploidy and Cancermentioning
confidence: 99%
“…TAM is characterised by increased circulating blast cells that harbor acquired N-terminal truncating mutations in the key hematopoietic transcription factor gene GATA1 (Wechsler et al 2002;Groet et al 2003;Rainis et al 2003;Bhatnagar et al 2016). Furthermore, the interaction between DS, GATA1 mutations and TAM was reported, recently (Banno et al 2016). TAM is usually self-limiting and undergoes spontaneous regression, but 10-20% of neonates with TAM subsequently develop myeloid leukemia in the first 5 years of life.…”
Section: Introductionmentioning
confidence: 99%